Osteopontin Blockade Attenuates Renal Injury after Ischemia Reperfusion by Inhibiting NK Cell Infiltration - Cen, Cindy (Shock, 2017)
Renal ischemia-reperfusion (RIR) injury is a common occurrence after major surgery and shock, leading to acute kidney injury (AKI). Osteopontin (OPN) is a secreted glycoprotein that acts as a proinflammatory cytokine and activator of T lymphocytes. We hypothesized that blockade of OPN reduces the severity of inflammation and injury in RIR. Renal ischemia was induced in adult C57BL/6 mice via bilateral clamping of renal pedicles for 35 min, followed by reperfusion for 24 h. Anti-OPN antibody (Ab), non-immunized isotype IgG, or normal saline was injected intravenously at time of reperfusion. Blood and kidneys were collected for analysis. At 24 h after RIR, OPN mRNA and protein levels were significantly increased in renal tissue compared to sham mice. In serum, elevated levels of BUN and creatinine were reduced in anti-OPN Ab-treated mice compared to vehicle. Anti-OPN Ab-treated mice also had decreased mRNA levels of injury markers neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule-1 (KIM-1) compared to the vehicle. The histologic architecture and apoptosis of renal tissue were improved in the anti-OPN Ab-treated mice. In renal tissue, inflammatory cytokines IL-6 and TNF-α protein levels were reduced in the Ab-treated mice. NK cell infiltration was decreased after anti-OPN Ab treatment, as was neutrophil infiltration, shown by reduced chemokine expression and Gr1 renal immunohistochemical staining. These findings demonstrate a beneficial role of OPN blockade in RIR associated with NK cell-mediated downregulation of inflammatory cytokines and chemokines. Administration of anti-OPN Ab may therefore serve as an immunomodulatory adjunct in the treatment of RIR-induced AKI.